MEMAHAMI FENOMENA CYBERBULLYING YANG DILAKUKAN USER TERHADAP SELEBRITI - Ayu Mila Ningrum; S. Rouli Manalu (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2019)
This study aims to find out the reason why someone does cyberbully to celebrities and to describe the forms of cyberbullying itself. In addition, this research also aims to find out the celebrity’s view about cyberbullying and to find out the response given by celebrities. This is motivated by the rise of cyberbullying by users towards celebrities on social media. Cyberbullying is generally interpreted as an act of intimidation or verbal violence committed by perpetrators through the internet or social networks. This study using the phenomenology approach using qualitative descriptive analysis method. With the phenomenology approach, this study seeks to understand a phenomenon of cyberbullying through the perspective of the perpetrators and victims. The subject of this study consisted of six informants who were divided into four actors and two victims by conducting in-depth interviews. The findings of this study are seen from the perspective of the perpetrators and celebrities as victims. The conclusion of this research shows that cyberbullying is based on socio-economic jealousy, lack of activity, to justify certain circumstances and humor. The researcher concluded that the existence of social media, especially fake accounts, made the perpetrators ventured to commit cyberbullying and cyberbullying as joint actions. Furthermore, it shows that legal risk can limit the occurrence of cyberbullying, but there is a rationalization of the perpetrators to continue to do cyberbullying. And the latest findings from the point of view of the perpetrators indicate that the actions of cyberbullying can bring forth replies from victims to the perpetrators. From a celebrity's point of view, researchers found that the occurrence of cyberbullying was driven by technology. In addition, cyberbullying also affects the mentality of celebrities and becomes a scary specter. Furthermore, this study also found that celebrities showed apathy and self-evaluation as an action to protect celebrities from cyberbullying. Finally, cyberbullying is a circular cycle, in a sense; celebrities experiencing cyberbullying also do cyberbully.